Theory of reality in development : essays in honour of Paul Streeten / edited by Sanjaya Lall and Frances Stewart (London, 1986)
This is a collection of essays in honour of the distinguished development economist, Paul Streeten, prepared by his friends and colleagues. Hugh Stretton traces Paul Streeten's intellectual development, showing that his contributions to economic thought invariably combine a scepti cism about preconceived theory together with a highly developed respect for reality. Each of the essays in this book exhibit this attitude while covering a wide range of subjects. Amartya Sen starts appropriately with a new look at Adam Smith. World stagflation is discussed by Wilfred Beckerman and by Michael Lipton. Mahbub ul Haq puts forward a case for an international debt refinancing facility. Jagdish Bhagwati and Richard Brecher analyse international invest ment. Sanjaya Lall discusses determinants of trade in services. Deepak Nayyar examines East-South trade. Nurul Islam considers the issues raised by world food security. Frances Stewart analyses lack of progress in North-South negotiations in general. The special problems of Latin America in the world economy are discus sed by Carlos Diaz-Alejandro. Gerald Helleiner looks at the effects of alternative trade strategies in Africa. Two essays are concerned with domestic issues in developing countries: Keith Griffin considers different systems of land tenure, while Jeffrey James discusses choice of technique in Tanzania's publicly owned firms. The scope of this volume-in terms of topic, geography and method of treatment-reflects Paul Streeten's own span. As well as representing important contributions on their own, the present contributions acquire unity from a similarity in approach-always giving priority to reality, if it comes into conflict with theoretical bias.
Keywords: Developing countries - Economic conditions